2018
DOI: 10.1039/c8nj00483h
|View full text |Cite
|
Sign up to set email alerts
|

Biologically activehalo-substituted ferrocenyl thioureas: synthesis, spectroscopic characterization, and DFT calculations

Abstract: The DNA binding affinity of ferrocenyl complexes explored by CV and UV ascertain them as noble DNA binders. The computational measurements correlate well with the outcomes of electrochemistry and bio-activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Following the same procedure, the following isothiocyanates were prepared: 2-bromobenzoyl isothiocyanate (1b), 75% yield; 4-methoxybenzoyl isothiocyanate (1c), 61% yield; 4-chlorobenzoyl isothiocyanate (1d), 64% yield, and 4bromobenzoyl isothiocyanate (1e), 78% yield. All compounds were confirmed by GC-MS analysis to be > 90% pure, with properties matching those previously published [15][16][17]. No attempts of further purification were made, due to their tendency to slowly decompose.…”
Section: Benzoyl Isothiocyanate (1a) a Representativesupporting
confidence: 76%
“…Following the same procedure, the following isothiocyanates were prepared: 2-bromobenzoyl isothiocyanate (1b), 75% yield; 4-methoxybenzoyl isothiocyanate (1c), 61% yield; 4-chlorobenzoyl isothiocyanate (1d), 64% yield, and 4bromobenzoyl isothiocyanate (1e), 78% yield. All compounds were confirmed by GC-MS analysis to be > 90% pure, with properties matching those previously published [15][16][17]. No attempts of further purification were made, due to their tendency to slowly decompose.…”
Section: Benzoyl Isothiocyanate (1a) a Representativesupporting
confidence: 76%
“…Asghar and coworkers 69 synthesized a series of ferrocene-based thioureas 91a–i and characterized them by spectroscopic techniques. It was found that the incorporation of the ferrocenyl group into thioureas is responsible for their enhanced lipophilic character.…”
Section: Applicationsmentioning
confidence: 99%
“…It is widely known that thiourea derivatives have antibacterial activity against planktonic bacteria. 28,29 Instead, microorganisms have the ability to create biological films (biofilms), which are complex communities of bacteria adhered to either a living or inert surface. In this situation, bacteria are more immune system, disinfectant, and antibiotic resistant than planktonic cells.…”
Section: Introductionmentioning
confidence: 99%